Central sensitisation as a predictor of self-management in chronic low back pain - Georgopoulos, Vasileios (2020)
Background: Chronic low back pain (CLBP) is one of the most prevalent reasons people seek healthcare assistance worldwide. Guidelines for managing CLBP prioritise the development of self-management strategies. Levels of central sensitisation (CS) may contribute to the relatively poor efficacy of treatments aiming to facilitate self-management. CS might be a dominant factor predicting worse self-management in people with CLBP following interventions aiming to improve such outcomes. Quantitative sensory testing (QST) may provide reliable and valid indices of CS and it may predict musculoskeletal pain and disability. CS might be associated with increasing psychological distress, pain, fatigue and catastrophisation which might also be predictors of ineffective self-management. CS has also been associated in people with knee pain with self-report measures of widespread pain distribution (reported by shading a pain manikin) or a self-report Central Mechanisms Trait score, comprising of items addressing depression, anxiety, neuropathic-like symptoms, pain distribution, catastrophising, sleep, fatigue and cognitive difficulties.